Social Media’s Influence on Students’ College Selection Processes - Pandeya, Yam Prasad (Shanti Journal, 2023)
Colleges have a keen interest in learning how students choose a college. In the present age of science and technology, young students are extremely influenced by social media. This influences how students make decisions while selecting colleges for their higher education. The main objective of this study was to explore the influence of social media on the college choice process of students in higher education. This study deployed a descriptive survey method under a quantitative research design. The sample was selected by stratified random sampling method. Education, Management, and Humanities faculties were considered as strata for this sampling purpose, within the strata, 270 students have been selected containing 90 students from each stratum using the simple random sampling method. The instrument used to collect the primary data for this study was a self-structured questionnaire. The questionnaire consisted of various structured items, including several four/five-point Liker t- scales, ranking scales, and multiple-choice questions. Descriptive analyses, t-test, and analyses of variance (ANOVAs) at 95% level of significance were used to identify the purpose of using ICT and effect of social media in college choice process of +2 students for their further study. The finding of this study shows that every faculty, gender, and ethnicity group students equally influenced by social media in their college choice process.